ANALYSIS OF HOUSING CONSTRUCTION TIME IN THE PURBALINGGA REGENCY AREA BY USING THE LINEAR SCHEDULING METHOD - Laksono, Taufik Dwi; Wiyanti, Dwi Sri (International Journal of Engineering Technologies and Management Research, 2024)
The realization of a construction project is closely connected to its cost and time. Work time planning illustrates the time of every work item from start to finish so that the total project completion time can be known. This study is a further analysis of the effects of using the linear scheduling method on total project time in a housing construction project to give a clear overview of potential differences. This study aimed to find the time needed to complete a housing project in Pubalingga Regency. Using LSM as a scheduling tool provides convenience in planning, executing, and controlling every work item, making it easier for the stakeholders to monitor the progress. This study concluded that using the Linear Scheduling Method (LSM), the time needed to complete 16 (sixteen) houses in Payodha Residence is 112 days